Decomposition of the Methylene Blue Dye Using Layered Manganese Oxide Materials Synthesized by Solid State Reactions - M. E. Becerra; A. M. Suarez; N. P. Arias; O. Giraldo (International Journal of Chemical Engineering)
The modulation in the synthesis parameters of layered manganese oxides allowed us to produce materials with different AC conductivities. These conductivities were correlated with the catalytic performance of the materials in the decomposition of methylene blue, as a model of electron transfer reactions. The manganese oxides were prepared by thermal reduction of KMnO4 at 400°C and 800°C where one sample was heated at 1°C/min and the other was heated at 10°C/min. The materials were characterized by atomic absorption, average oxidation states of manganese, X-ray diffraction, thermogravimetric analysis, and scanning electron microscopy. The results indicate that, by increasing the synthesis temperature, both the lamellar arrangement and the crystal size increased, while the Mn4+ amount in the material decreased. Furthermore, it was observed that as the conductivity increases for the materials, the catalytic performance also increases. Therefore, a direct correlation between the conductivity and catalytic performance can be established. For example, the layered manganese oxides material synthesized at 400°C, using a heating rate of 10°C/min, showed the highest AC conductivity and had the best performance in the degradation of methylene blue. Finally, we propose a general mechanism for understanding how manganese oxides behave as catalysts that produce oxidizing species from H2O2 which degrades methylene blue. Our proposed mechanism takes into consideration the state of aggregation of the catalyst, the availability of Mn4+, and the electrical conductivity.